HRH The Crown Prince of Denmark. - Ward, Leslie, Sir, 1851-1922 (also known as spy) (Day & Son, 1895)
Scholarly notes may be added at a later date.
Vanity Fair, Dec 12 1895.
1 print : col.
Keywords: Caricatures; Cartoons; Royal family, Denmark